(untitled) (Advances in Military Technology, 2021)
This article presents a method to establish the dynamic model of the Shooter-weapon system when firing based on Lagrange’s theorem and the theory of multibody system dynamics, in which the influence of the human body was taken into account. In the dynamic model, the influence of the gunner is solved by using elastic-damping links in the x, y and z axes. The dynamic model is created for a portable gas-operated submachine gun and contains three solids with seven degrees of freedom. The 7.62 mm AKM submachine gun has been used for the model simulation and experimental verification. The dynamic simulation was conducted and then the results were compared with the corresponding experimental data. The model simulation results are very close to the experimental results. This study aims to survey the influence of various parameters on gun stability in the shooting. It is possible to apply these results to portable automatic guns.